Pencegahan Stunting Melalui Penyuluhan Pemberian Makanan Tambahan pada Anak Balita di Wilayah Kerja Puskesmas Bontomangape, Kabupaten Takalar - Rosdianah Rosdianah; Irmawati.S; Maria ana Marlina; Eka Wardani (Compromise Journal Community Proffesional Service Journal, 2024)
Stunting is a problem that is increasingly found in developing countries, including Indonesia. According to the United Nations International Children's Emergency Fund (UNICEF), one in three children is stunted. The aim of this community service activity is to provide additional food to children under five. The method used was lectures and questions and answers to mothers about eating tambhana. This activity was carried out in the Bonomangape Village Office Room, Takalar Regency on June 10 2024, which was attended by 12 mothers who have toddlers. The results of supplementary feeding activities using leaflets and plipcharts on supplementary feeding behavior showed that only 4 people (33.33%) had good knowledge in the pre-test knowledge, and after education and mentoring, then a post-test was carried out, those who had good knowledge increased to 10 people (83.33%) so that by providing education and mentoring will increase motivation and change behavior in providing additional food to toddlers